O prostoru u srpskoj jezičkoj slici sveta - Piper, Predrag (Slavistična revija, 2014)
The paper deals with the configuration of the semantic category of space in the linguistic picture of the world verbalized and grammaticalized in the subsystems of contemporary standard Serbian prepositions, prefixes, adverbs, and adjectives with the meaning of spatial relations. It also discusses the question of comparing structurally related subsystems within the same language.
Keywords: adjectiv; adverb; comparative studies; predlog; predpone; prefixial compound; preposition; pridevnik; primerjalne študije; prislov; prostor; Serbian langauge; space; srbščina